The anti-osteoporotic effect of Moringa oleifera leaves extract on glucocorticoids-induced jawbone osteoporosis in Albino rats - Soliman, Tasneem; Ali, Zoba; Zayed, Mohamed; Sabry, Dina; AbuBakr, Nermeen (Brazilian Dental Science, 2021)
Objective: Glucocorticoids induced osteoporosis and its related fragility fractures represent a costly human and socioeconomic load worldwide. All the current pharmacological therapies possess multiple adverse effects and high cost. Thus, the pesent study aimed to evaluate the bone healing ability of Moringa oleifera (MO) on glucocorticoids induced osteoporosis in the jawbone of Albino rats. Material and Methods: Osteoporosis was prompted by a daily intraperitoneal injection of 200 micro g/ 100 g dexamethasone for 30 days. Next,the animals were randomly divided into 2 groups; osteoporotic and MO treated group. The treated group receivd a daily oral dose of 200mg/kg of MO. Rats from the MO group were sacrificed after 4 weeks from the beginning of treatment, and the same sacrifice date was used for the osteoporotic group. Bone regeneration was evaluated by dual energy x-ray absorptiometry (DEXA), real time polymerase chain reaction (RT-PCR), histopathological and histomorphometric examination. Results: After the sacrifice, the DEXA analysis revealed a significant upregulation in the BMD in the MO treated group (p <0.001). The RT-PCR test showed a significant decline in RANKL gene expression and a significant rise in OPG gene expression in the MO group (p < 0.001, p = 0.002, respectively). The histopathological examination of the MO group displayed a marked healing of the jawbone micro-anatomy. The histomorphometric analysis also showed that the bone area percentage increased significantly in the MO group (p <0.05). Conclusion: A cheap, easy to get, yet a powerful plant like MO leaves, can be cosidered an effective treatment for osteoporosis. KEYWORDS Bone regeneration; Glucocorticoids; Moringa oleifera; Osteoporosis.